A Corpus-based Study of Textual Metaphor in English. Issue 3 (3rd July 2017) - He, Qingshun; Wen, Binli
Abstract : Following the criterion of double functionality for identifying grammatical metaphor, this research investigates the diachronic and genre distributions of two of the five types of textual metaphor proposed by He et al .: conjunctionalization of conjunctive adverbial groups and prepositionalization of hypotactic conjunction groups. Research based on COHA reveals that: (1) the conjunctionalization of conjunctive adverbial groups agrees with the principle of unidirectional transfer of grammatical metaphor, and during the recent century conjunctive adverbial groups have been experiencing a trend of conjunctionalization; (2) conjunctive prepositions, however, are not directly transferred from hypotactic conjunction groups but are induced by the gerundalization of present participles; and (3) hypotactic conjunction groups will transfer to zero hypotactic conjunction groups, resulting in a new member of textual metaphor. Research based on COCA and BNC shows that both conjunctionalization of conjunctive adverbial groups and prepositionalization of hypotactic conjunction groups tend to occur in informal texts. This confirms the point of view that paratactic clause complexes are favoured in informal genres such as Spoken and Fiction and that simple clauses win out in formal texts due to the wide use of nominalization of verbal groups and verbalization of conjunction groups.